The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1101/750216
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Marker-assisted introgression of multiple resistance genes confers broad spectrum resistance against bacterial leaf blight and blast diseases in Putra-1 rice variety

Abstract: This experiment was conducted with the aim of introgressing multiple resistance genes against bacterial leaf blight (BLB) and blast diseases through marker-assisted backcross breeding. Two dominant (Xa4 and Xa21) and two recessive (xa5 and xa13) BLB resistance genes were introgressed into a Malaysian elite rice variety Putra-1 with genetic background of three blast resistance (Piz, Pi2 and Pi9) genes and high yielding. Eight polymorphic tightly linked functional and SSR markers were used for foreground selecti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 48 publications
2
4
0
Order By: Relevance
“…These markers revealed the highest PIC values and gave the same values 1.00 and the highest number of alleles ranging from 8 to 9 alleles per locus, suggesting that these markers could be used for molecular characterization of a large number of rice genotypes rather than mapping populations for drought tolerance. The results were similar to those obtained by [ 10 , 51 , 52 ].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…These markers revealed the highest PIC values and gave the same values 1.00 and the highest number of alleles ranging from 8 to 9 alleles per locus, suggesting that these markers could be used for molecular characterization of a large number of rice genotypes rather than mapping populations for drought tolerance. The results were similar to those obtained by [ 10 , 51 , 52 ].…”
Section: Resultssupporting
confidence: 91%
“…In contrast to morphological traits, molecular markers can reveal large differences among genotypes at the DNA level, providing a more direct, reliable, and efficient tool for germplasm characterization, conservation, and management and untouched by environmental influence [ 9 ]. SSR markers can detect a high level of allelic diversity, and they have been extensively used to identify genetic variation among rice subspecies [ 10 ]. Simple sequence repeats (SSR) markers are efficient in detecting genetic polymorphisms and discriminating among genotypes from germplasms of various sources; even they can notice the finer level of variation among closely related breeding materials within the same variety [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was also reported that Abhaya was found to be resistant against blast (blast SES score ranged from 1 to 3 with different isolates) (Sinha et al 2017) isolates. Similarly, IRBB60 was also reported to have moderately resistant reaction with blast (with blast SES score of 3) (Chukwu et al 2020). While working with BLB, the challenge appears to be more due to the presence of the number of genetically distinct virulent Xoo strains in different geographical locations (Midha et al 2017).…”
Section: Discussionmentioning
confidence: 94%
“…Molecular markers could reveal significant differences among genotypes at the level of DNA in contrast to morphological characteristics, providing a more effective, accurate and efficient instrument for the characterization, conservation and management of germplasm and untouched by environmental influence (Singh and Sengar, 2015). SSR markers can detect a high degree of allelic diversity, and it have been widely used to identify genetic variation among rice subspecies (Chukwu et al, 2020). Simple sequence repeat (SSR) markers are successful in detecting genetic polymorphisms and distinguishing between genotypes from different sources of germplasm, they can also detect the finer level of variation within the same variety among closely related breeding materials (Lapitan et al, 2007).…”
Section: Introductionmentioning
confidence: 99%